2017
DOI: 10.3389/fendo.2017.00002
|View full text |Cite
|
Sign up to set email alerts
|

Non-Genomic Actions of the Androgen Receptor in Prostate Cancer

Abstract: Androgen receptor (AR) is a validated drug target for prostate cancer based on its role in proliferation, survival, and metastases of prostate cancer cells. Unfortunately, despite recent improvements to androgen deprivation therapy and the advent of better antiandrogens with a superior affinity for the AR ligand-binding domain (LBD), most patients with recurrent disease will eventually develop lethal metastatic castration-resistant prostate cancer (CRPC). Expression of constitutively active AR splice variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
86
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 82 publications
1
86
0
1
Order By: Relevance
“…Estrogen-activation of the GPERs (and likely membrane-associated ERs, as well) initiates PI3K/AKT and MAPK/ERK signaling pathways ( 13 ), that in turn coordinate the transcription and translation of whole gene families that regulate cellular processes including, but not limited, to cellular differentiation, proliferation, survival, and apoptosis ( 14 ). Similarly, androgens and progesterones exert their functional effects on transcription and translation through intracellular canonical genomic signaling and the non-genomic signaling cascades PI3K/AKT and MAPK/ERK ( 15 , 16 ). Differential androgen signaling depends on cytoplasmic- versus membrane-targeted isoforms of the androgen receptor gene ( 16 ).…”
Section: Sex Steroid Biosynthesis and Signaling Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen-activation of the GPERs (and likely membrane-associated ERs, as well) initiates PI3K/AKT and MAPK/ERK signaling pathways ( 13 ), that in turn coordinate the transcription and translation of whole gene families that regulate cellular processes including, but not limited, to cellular differentiation, proliferation, survival, and apoptosis ( 14 ). Similarly, androgens and progesterones exert their functional effects on transcription and translation through intracellular canonical genomic signaling and the non-genomic signaling cascades PI3K/AKT and MAPK/ERK ( 15 , 16 ). Differential androgen signaling depends on cytoplasmic- versus membrane-targeted isoforms of the androgen receptor gene ( 16 ).…”
Section: Sex Steroid Biosynthesis and Signaling Mechanismsmentioning
confidence: 99%
“…Similarly, androgens and progesterones exert their functional effects on transcription and translation through intracellular canonical genomic signaling and the non-genomic signaling cascades PI3K/AKT and MAPK/ERK ( 15 , 16 ). Differential androgen signaling depends on cytoplasmic- versus membrane-targeted isoforms of the androgen receptor gene ( 16 ). By contrast progesterone receptors, like estrogen receptors, are encoded by distinct genes and include the intracellular receptors PR-A and PR-B and the membrane progesterone receptor isoforms alpha (mPRα), beta (mPRβ), and gamma (mPRγ) ( 17 ).…”
Section: Sex Steroid Biosynthesis and Signaling Mechanismsmentioning
confidence: 99%
“…Several studies have demonstrated that the AR can be stimulated by high cAMP levels. AR transactivation by androgens could be enhanced by forskolin and other activators of adenylate cyclase in AR-transfected monkey kidney CV-1 cells or PC3 cells (1,12). The increase in AR transcription was caused by enhanced AR-DNA binding and was not due to an increase in AR protein expression (1).…”
mentioning
confidence: 99%
“…While still in the cytoplasm, AR can bind to several proteins and activates SRC, RAS, MAPK, AKT, EGFR, and PI3K among others Hellen Kuasne and Mateus C. Barros-Filho contributed equally to this work. [7,8]. Non-genomic AR signaling promotes tumor cell survival, proliferation, migration, invasion, and metastasis [9].…”
Section: Introductionmentioning
confidence: 99%